A Preliminary Study of the Effect of Mobile-Based Education on Dental Students' Learning in Practical Course of Oral Pathology - mostafa babazadeh-kamangar; iman jahanian; hemmat gholinia (Zanjan University of Medical Sciences and Health Services, 2017)
Background and Objective: Mobile has provided a valuable teaching/learning opportunity for professors and students. Mobile electronic books are one of the educational resources that there is no defined plan for their usage at universities of medical sciences in Iran. This research aimed to evaluate mobile-based education for practical course of oral pathology. Materials and Methods: Oral pathology course was provided in the form of PowerPoint files and images and office suite was used to run these files. 30 general dentistry students in their sixth semester were divided into two equal groups. At first stage, a group of students were taught traditionally and another group through their mobile phones. Then, an examination was conducted to evaluate the traditional teaching (classroom) and m-learning (mobile learning) in these two groups. At second stage, the two groups were replaced but the contents didn't change. Afterwards, a re-evaluation of traditional teaching and m-learning was done. In the end, the effects of these two methods of teaching on students' learning were compared using statistical methods. Results: Results showed that mobile-based teaching significantly affected students' final scores (P<0.05) and mean scores of the two groups in mobile-based teaching were significantly higher than mean scores of the two groups in traditional teaching. Conclusion: Mobile-based teaching can be used as a teaching aid in traditional classroom educations.